CLASSIFICATION OF THE SEVERNAYA DVINA RIVER AND THE VYCHEGDA RIVER CHANNEL SECTIONS ACCORDING TO COMPLEXITY OF CHANNEL PROCESSES AND THEIR MANAGEMENT CONDITIONS - Nadezhda M. Mikhailova; Roman S. Chalov (Водное хозяйство России: проблемы, технологии, управление)
The complexity of the control conditions for channel processes is examined by the case of the Severnaya Dvina River and its main tributary the Vychegda River, which are both the most important waterways of the European North of Russia. The developed and approved earlier methodology was applied to rank rivers in by the channel stability, the load and composition of sediments (the factor was applied for the first time to the rivers under study), water capacity, geological and geomorphological conditions of the channel formation conditions (embedded riverbeds or channels with wide floodplain), evolution of different morpho/dynamic types of channel, abundance and mode of deformations of riffles. The latter factor controls both possibility and features of regulative works when designing activities in water economics, navigation and construction. The data on the sediment amounts dredged from riverbeds to ensure the waterway functioning are demonstrated to be the integral estimation of the control conditions for channel processes.